SCREENING OF INDIGENOUS BACTERIA FROM RHIZOSPHERE OF MAIZE (ZE A MAYS L.) F OR THEIR PLANT GROWTH PROMOTION ABILITY AND ANTAGONISM AGAINST FUNGAL AND BACTERIAL PATHOGENS - U. Farooq; A. Bano (Journal of Animal and Plant Sciences, 2013)
During present investigation, bacterial strains were isolated from rhizosphere of healthy and infected fields of maize grown at Yousafwalla, Pakistan. Fourteen isolates were screened for their antibacterial and antifungal activities. Three isolates showed the antimicrobial activity against Pseudomonas aeruginosa and Bacillus subtilis. Staphylococcus aureus and Klebsiella pneumoniae were found to be resistant to all the rhizobacteria except YCH1 which inhibits the growth of Staphylococcus aureus by 47%. All the strains exhibited maximum inhibition against Fusarium moniliforme. The Yys and YiBa were found to be most potent antagonist against Fusarium moniliforme showing maximum inhibition by 74%. The bacterial isolates were not much effective in inhibition of the Aspergillus flavus and Helminthosporium sativum used in this study. It was found that the bacterial isolates which showed siderophore production also exhibited higher antifungal activity. All the isolates were catalase and oxidase positive solubilize phosphorus and produce bacteriocin. Bacterial strains were further evaluated as bioinoculant on maize (Zea mays L). The four selected isolates showed significant (P < 0.05) increase in dry matter production, plant height and root length of maize. The present study suggests the implication of PGPR isolates YDYs, Yys, YiH and Yipe as bioinoculant for biofertilizers.
Keywords: Antifungal; Antibacterial; Phosphorus soloubilization; bacteriocin production